Hybrid organic-inorganic coatings via electron transfer behaviour - Wail Al Zoubi (Nature Portfolio, 2017)
Abstract A novel method to functionalize the surface of inorganic coating by growing organic coating has been investigated based on microstructural interpretation, electrochemical assessment, and quantum chemical analysis. For this purpose, inorganic coating with magnesium aluminate, magnesium oxide, and titanium dioxide was prepared on magnesium alloy via plasma electrolytic oxidation (PEO), and, then, subsequent dip-coating method was used to tailor organic coating using diethyl-5-hydroxyisophthalate (DEIP) as organic molecules. The incorporation of TiO2 particles worked as a sealing agent to block the micro-defects which resulted mainly from the intense plasma sparks during PEO. In addition, such incorporation played an important role in enhancing the adhesion between inorganic and organic coatings. The use of DEIP as organic corrosion inhibitor resulted in a significant decrease in porosity of inorganic coating. Quantum chemical calculation was used to clarify the corrosion inhibition mechanism which was activated by introduction of DEIP. Thus, the electrochemical analysis based on potentiodynamic polarization and impedance spectroscopy tests in 3.5 wt% NaCl solution suggested that corrosion resistance of magnesium alloy sample was enhanced significantly due to a synergistic effect arising from the hybrid inorganic and organic coatings. This phenomenon was explained in relation to electron transfer behaviour between inorganic and organic coatings.